HCI-enriched approach for DSS development: the UP/U approach - Ltifi, H.; Ben Ayed, M.; Kolski, C.; Alimi, A.M. (2009 IEEE Symposium on Computers and Communications, 2009)
In this paper we propose an approach aiming to integrate human-computer interaction (HCI) aspects in decision support system (DSS) development. We propose an approach combining two methods: one issued from software engineering field (the rational unified process) and the other one from the HCI field (the U model). We have tested our approach in a DSS set up in the healthcare domain: the supervision of nosocomial infections in an intensive care unit.